Podcast towards Students’ Listening Comprehension: A Literature Review - Safitri, Isnaini Amanda; Najwa, Siti (Cipta Pustaka Nusantara, 2024)
Listening comprehension remains a challenging skill for many English learners. This research investigates the effectiveness of podcasts as a tool for developing listening skills in students. Using a SLR (Systematic Literature Review), this article analyzed three studies from 2018-2023 exploring the impact of podcasts on student listening comprehension. Findings reveal a significant improvement in listening skills across all studies, regardless of student levels or contexts. The researchers attributed this success to several factors: (1) authentic material, (2) diverse content, (3) active listening activities. Based on these findings, this article conclude that podcasts offer a valuable and engaging tool for improving listening comprehension in English language learning.